FORMULATION AND EVALUATION OF FAST DISSOLVING TABLETS OF BUSPIRONE USING COPROCESSED SUPERDISINTEGRANTS - SHARMA, SHALLY; SETH, NIMRATA; GILL, NARESH SINGH (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present study aims to formulate and evaluate Fast dissolving tablet of Buspirone, the drug that is used for management of anxiety, by direct compression method using various Super disintegrants. Methods: Ten formulations (F1-F10) of fast dissolving tablets of Buspirone were prepared by using various Superdisintegrants. The prepared tablets were evaluated for hardness, friability, thickness, drug content uniformity, water absorption, wetting time, and disintegration time and in vitro dissolution study. Results: Among all the formulations, F10 (containing 5 mg of Coprocessed (CS: SSG 1:2) Superdisintegrants) was considered to be the best formulation, which released up to 98% drug in 20 min as compared to a marketed conventional dosage form which dissolves in approx 60 min. The results of stability study of formulation F10 after a period of two months indicated that the formulation was stable. Conclusion: It was concluded that a fast-dissolving tablet of Buspirone containing various Superdisintegrants is better and effective to meet patient compliance.